2010
DOI: 10.1111/j.1447-0756.2009.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α, interleukin‐6 and interleukin‐10 polymorphisms in preeclampsia

Abstract: Because women with IL-10 (-1082) AA genotype have 3.38-fold increased risk of developing PE according to GG genotype (95% CI 1.21-9.4, P = 0.01), we suggest that IL-10 (-1082) variant A allele is associated with an increased risk of preeclampsia, which is independent from its metabolic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
4
52
1
Order By: Relevance
“…Previous investigations have tested the association between IL-10 gene polymorphisms and preeclampsia development, but with conflicting results (Stonek et al, 2008;Vural et al, 2010;Valencia Villalvazo et al, 2012;Pissetti et al, 2014;Sowmya et al, 2014;Song and Zhong, 2015;Liu et al, 2015). Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have tested the association between IL-10 gene polymorphisms and preeclampsia development, but with conflicting results (Stonek et al, 2008;Vural et al, 2010;Valencia Villalvazo et al, 2012;Pissetti et al, 2014;Sowmya et al, 2014;Song and Zhong, 2015;Liu et al, 2015). Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study of 177 preeclamptic pregnant women and 182 controls, Song and Zhong (2015) found that the IL-10 -592A/C SNP elevated risk of early-onset preeclampsia in a Chinese population. In addition, Pissetti et al (2014) and Vural et al (2010) carried out an investigation involving expectant women in Turkey and Brazil, revealing that the IL-10 -1082A/G sequence variant is associated with preeclampsia susceptibility. However, Valencia Villalvazo et al (2012) and Stonek et al (2008) failed to detect a correlation between this condition and polymorphisms in IL-6 and IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that the results of studies seeking associations of these polymorphisms with PE have not always been consistent in different population analyses (Hefler et al, 2001;Lachmeijer et al, 2002;de Groot et al, 2004;Haggerty et al, 2005;Stonek et al, 2008;Vural et al, 2010), and the Mestizo and Amerindian populations are genetically heterogeneous, the principal aim of this study was to analyze the possible association between rs1800896 of IL-10, rs1800795 of IL-6 and the VNTR in intron 2 of IL-1Ra, as well as gene-gene interactions between these three polymorphisms with the presence of PE in Mexican-Mestizo women and one Amerindian population from México (Maya).…”
mentioning
confidence: 99%
“…146 Polymorphisms of cytokine genes may increase the risk of developing preeclampsia. 147 Peripheral blood mononuclear cells and decidual lymphocytes express higher levels of Th1 cytokines, including TNFα, and lower Th2 cytokine expression in preeclampsia compared to normal pregnancy. 148,149 This is reflected in the maternal circulation, with a further rise in pro-inflammatory cytokines such as TNFα, accompanied by an elevated level of soluble receptor in an attempt to dampen the cytokine response.…”
Section: Tnfα and Preeclampsiamentioning
confidence: 99%